Rare case of acute abdomen: Right colon perforation due to the colon diverticulitis - Faruk Pehlivanli; Gökhan Karaca; Oktay Aydin; Sevilay Vural; Figen Coskun (Apollo Medicine)
Colonic diverticula and related complications are common pathologies in elderly patients. In older patients, colonic diverticulum perforation is more common in the sigmoid colon, whereas right colon diverticulum perforation is rather rare. In younger patients, especially in patients under 30 years of age, right colon diverticula are more common than left colonic diverticula. Therefore, right colon diverticulum perforation should be considered in patients with acute abdomen in this age group. In this case, right column diverticulum perforation is presented in a patient with acute abdomen findings.